Copper‐Catalyzed Direct Arylselenation of Anilines by CH Bond Cleavage. Issue 5 (25th February 2015) - Ricordi, Vanessa G.; Thurow, Samuel; Penteado, Filipe; Schumacher, Ricardo F.; Perin, Gelson; Lenardão, Eder J.; Alves, Diego
Abstract We describe here an efficient and regioselective synthesis of arylselanyl anilines by copper‐catalyzed direct arylselenation of arylamines. Using a catalytic amount of copper iodide in dimethyl sulfoxide at 110 °C under an air atmosphere, a range of arylselanyl anilines was obtained directly from substituted diaryl diselenides in moderate to good yields via CH bond cleavage of aryl amines. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>